Increasing Learning Motivation Through The Use Of Clinical Examples In Biochemistry - Sharifov Akmal Halimovich (American Journal of Applied Science and Technology, 2025)
This article examines the pedagogical value of using clinical examples in teaching biochemistry and their impact on learning motivation. Real-life situations in a clinical context help students connect theoretical knowledge with practice, develop analytical thinking and independent work skills. The article also highlights the possibilities of effectively organizing lessons through interactive methods, virtual laboratories, and situational games. The results of the study show that the use of clinical examples increases learning motivation, makes lessons more interesting, and makes biochemistry more understandable for students.